(untitled) (Research, Society and Development, 2021)
Social networks have grown exponentially in recent decades as a means of work and, with them, the use of applications for health promotion. Although the current health care model is still centered on individual curative care, the importance of changing to preventive care is noted, as this alone has not solved the population’s health problems. Cancer is a concern among health professionals because it is a disease that has a silent advance and individuals are diagnosed in an advanced state, demonstrating the importance of stimulating prophylactic care. The media, to the detriment of technological advances, can be used as health promotion strategies in oncology as they enable the globalization of information generated in real time. Thus, it allows people with different sociocultural contexts to interact, contributing to the learning process becoming more effective, reliable and less boring, thus providing a better elaboration on coping strategies and problem solving that need to be overcome by society. The project aimed to mobilize the general public, including students and employees of the Cesmac University Center, to seek a more aware relationship about cancer. Health education classes and activities were held covering the areas of dentistry, medicine, nutrition, psychology and nursing. The actions were carried out through classes on the Microsoft teams digital platform with several guests, a multidisciplinary therapeutic management discussion group and informative posts on the Instagram digital platform.